2018
DOI: 10.3390/su10072477
|View full text |Cite
|
Sign up to set email alerts
|

From Awe to Ecological Behavior: The Mediating Role of Connectedness to Nature

Abstract: Awe is a self-transcendent emotion that can diminish one's focus on the self and serves as an important motivator of commitment to social collectives. However, the influence of awe on ecological behavior is not clear. This study examines the relationships between people's feeling of awe, their connectedness to nature, and ecological behavior. Three experiments tested the effect of awe on ecological behaviors including mediation tests. Compared with participants in the control condition, participants in the awe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
76
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(84 citation statements)
references
References 46 publications
(74 reference statements)
7
76
1
Order By: Relevance
“…Along these lines, recent work by Moreton, Arena, Hornsey, Crimston, and Tiliopoulos (2019) found across two studies that moral elevation increased feelings of connectedness to nature. These findings provide further evidence for the role of social cognition in connectedness to nature, and, along with Yang et al (2018) provide the most direct evidence suggesting that self-transcendent positive emotions can facilitate connectedness to nature. However, although this research suggests that awe and related emotions may increase connectedness to nature, no published research to date has investigated whether other social emotions may help facilitate bonds with the natural world.…”
Section: Self-transcendent Emotions and Connectedness To Nature 16supporting
confidence: 61%
See 1 more Smart Citation
“…Along these lines, recent work by Moreton, Arena, Hornsey, Crimston, and Tiliopoulos (2019) found across two studies that moral elevation increased feelings of connectedness to nature. These findings provide further evidence for the role of social cognition in connectedness to nature, and, along with Yang et al (2018) provide the most direct evidence suggesting that self-transcendent positive emotions can facilitate connectedness to nature. However, although this research suggests that awe and related emotions may increase connectedness to nature, no published research to date has investigated whether other social emotions may help facilitate bonds with the natural world.…”
Section: Self-transcendent Emotions and Connectedness To Nature 16supporting
confidence: 61%
“…However, recent work by Yang, Hu, Jing, and Nguyen (2018) found that awe increased connectedness to nature, even when awe was not elicited by nature, but rather was elicited by other humans. These studies provide some of the most direct evidence to date linking selftranscendent positive emotions to connectedness to nature.…”
Section: Self-transcendent Emotions and Connectedness To Nature 16mentioning
confidence: 95%
“…In the present research, we focus on another factor, the awe emotion, that could influence conspicuous consumption as well. Given that awe could draw attention from an individual’s self‐interest and concern to entities that are vaster than the self (Piff et al, ; Yang, Hu, Jing, & Nguyen, ), it is reasonable to expect that awe could alleviate the inclination to conspicuous consumption, which is a typical self‐oriented and self‐focused behavior. This assumption could be deduced when we identify both the features of awe and the drivers of conspicuous consumption.…”
Section: Literature Reviewmentioning
confidence: 99%
“…From this point of view, the awe experience makes individuals look down upon the materialistic motivation of (conspicuous) consumption. Secondly, awe, as a typical self‐transcendent emotion, enhances the connectedness of the unity (Bonner & Friedman, ; Shiota, Keltner, & Mossman, ; Yang et al, ), which in turn increases the possibility to make decision for the interests of all the unity (e.g., the society, the natural world) instead of oneself. Awe, accompanied with a small self (Piff et al, ), will make individuals put value of the collective well‐being in a more important position than the self’s well‐being.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Closeness to nature was the second lowest-rated SWB dimension after Belief in God, whereas the environmental pillar at the local level was the highest-rated SD. While connectedness to nature is only weakly correlated (r = 0.18) with the level of SWB [55], several authors argue that sustainability, based on a paradigm change from a consumer lifestyle to an eudemonic type of existence, is only possible if the broken relationship between nature and humans is re-established [107]. Since Rousseau, several thinkers pointed out how our disconnection from nature, or desperate effort to dominate it, that is, the desacralization of nature, is at the root of our sustainability crisis [108].…”
Section: Discussionmentioning
confidence: 99%